FEASIBILITY ANALYSIS OF COMPETENCY TRAINING MODEL RESEARCH INSTRUMENTS RESIDENTIAL CONSTRUCTION WORKERS WHO HAVE LOCAL WISDOM VALUES - Purnamawati; UTIARAHMAN, ARFAN; Yahya, Muhammad (Jurnal Vokasi Keteknikan, 2024)
The aim of this research is to analyze the feasibility of research instruments that will be used in developing a design for a competency training model for residential construction workers that has local wisdom values. The research method, namely analyzing the validity and reliability of research instruments, aims to determine the level of validity of research instruments before they are used to describe the implementation of learning. Analysis of validation results was carried out using quantitative methods by providing assessments by 6 experts or experts. The research results show that the instruments used in the research on the competency training model for residential construction workers which have local wisdom values obtained a mean value of > 0.90 including very high validity and reliability which shows that these instruments are suitable for use.